Investigation of Potential Effects of Ibuprofen on the Storage Cells and Anhydrobiosis Capacity of the Tardigrade Paramacrobiotus experimentalis - Aleksandra Miernik; Filip Wieczorkiewicz; Sebastian Student; Izabela Poprawa (Diversity, 2024)
The surge in pharmaceutical consumption, particularly non-steroidal anti-inflammatory drugs (NSAIDs) such as ibuprofen, has raised concerns about their presence in aquatic ecosystems. This study investigated the potential ecological impact of ibuprofen, focusing on the ultrastructure of storage cells in the tardigrade Paramacrobiotus experimentalis, renowned for its resilience to environmental stressors. Individuals were exposed to three ibuprofen concentrations (0.1 μg/L, 16.8 μg/L, and 1 mg/L) over 7 and 28 days. Storage cells were examined using light microscopy, transmission electron microscopy, and confocal microscopy. This study also explored ibuprofen’s impact on the process of anhydrobiosis. In the short-term experiment, no ultrastructural changes in tardigrade storage cells were observed across ibuprofen concentrations. However, in the long-term incubation, autophagic structures in storage cell cytoplasm were identified, indicating potential adaptive responses. Individual mitochondria exhibited degeneration, and the rough endoplasmic reticulum displayed slight swelling. No evidence of increased oxidative stress or nuclear DNA fragmentation was observed in any research group. This study elucidates the complex responses of tardigrade storage cells to ibuprofen exposure. The findings emphasize the importance of understanding pharmaceutical impacts on aquatic organisms, highlighting the resilience of tardigrades to specific environmental stressors.